Engineering a highly selective, hemoprotein-based scavenger as a carbon monoxide poisoning antidote with no hypertensive effect - Matthew R. Dent; Anthony W. DeMartino; Qinzi Xu; Xiukai Chen; Alay Gandhi; Hyon S. Hwang; Kaitlin A. Bocian; Jacob E. Correnti; Youmna Abdelghany; Elmira Alipour; K. Burak Ucer; Stephen R. Baker; et al. (Proceedings of the National Academy of Sciences, 2025)
Carbon monoxide (CO) poisoning causes 50,000 to 100,000 emergency department visits and ~1,500 deaths in the United States annually. Current treatments are limited to supplemental and/or hyperbaric oxygen to accelerate CO elimination. Even with oxygen therapy, nearly half of CO poisoning survivors suffer long-term cardiac and neurocognitive deficits related to slow CO clearance, highlighting a need for point of care antidotal therapies. Given the natural interaction between CO and ferrous heme, we hypothesized that the hemoprotein RcoM, a transcriptional regulator of microbial CO metabolism, would make an ideal platform for CO-selective scavenging from endogenous hemoproteins. We engineered an RcoM truncate (RcoM-HBD-CCC) that exhibits high CO affinity ( K a,CO = 2.8 × 10 10 M −1 ), remarkable selectivity for CO over oxygen ( K a,O2 = 1.4 × 10 5 M −1 ; K a,CO / K a,O2 = 1.9 × 10 5 ), thermal stability (T m = 72 °C), and slow autoxidation rate ( k ox = 1.1 h −1 ). In a murine model of acute CO poisoning, infused RcoM-HBD-CCC accelerated CO clearance from hemoglobin in red blood cells (RBCs) and was rapidly excreted in urine. Moreover, infused RcoM-HBD-CCC elicited minimal hypertension in mice compared to infused globins (hemoglobin, myoglobin, and neuroglobin), attributed to a comparatively limited reactivity toward nitric oxide (NO) via dioxygenation [ k NOD (RcoM) = 6 to 8 × 10 6 M −1 s −1 vs k NOD (Hb) = 6 to 8 × 10 7 M −1 s −1 ]. These data suggest that RcoM-HBD-CCC is a safe, selective, and efficacious CO scavenger. By limiting hypertension through minimal NO scavenging, RcoM-HBD-CCC improves end-organ adverse effects compared with other hemoprotein-based therapeutics.